Sintesis dan Uji Senyawa 3,3’-dihidroksi-4,4’-dimetoksidibenzilidenaseton sebagai Bahan Aktif Tabir Surya dan Antioksidan - Harizal Harizal; Ariyo Prabowo Hidayanto; Nindya Wulan Sari (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2018)
Synthesis and preliminary evaluation of 3,3’-dihydroxy-4,4’-dimethoxydibenzylidenacetone (DDB) as sunscreen and antioxidant have been successfully conducted. The compound was prepared throught acid catalyzed condensation reaction between vanillin and aceton using saturated HCl solution in glacial acetic acid. Pre-evaluation of sunscreen active compound candidate was performed by determining electronic absorbance profile, lamdamax, e, lamda c, UVA/UVB ratio, and photostability. While antioxidant activity test was performed using DPPH radical scavenger method. Based on the results obtained, the compound obtained has very good protective effect in UVA regions with high antioxidant activity.